A social realist account of the emergence of a formal academic staff development programme at a South African university - Quinn, Lynn (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2007)
Using social realist theory and particularly the morphogenetic/morphostatic methodology advocated by Margaret Archer, this study offers a critical examination of the emergence of a formal academic staff development programme at a small South African university (SSAU). Archer's morphogenetic approach enabled an investigation of the interface between culture, structure and agency (at macro, mezo and micro levels) in order to theorize about the material, ideational and agential conditions that obtained and which in turn enabled the emergence of the Postgraduate Diploma of Higher Education (PGDHE) at the SSAU. The study therefore advances concrete propositions about the cultural, structural and agential conditions for transformation which existed at a particular time in the history of higher education (and the subfield of educational development) which enabled the introduction of the PGDHE. Analysis of the data suggests that what occurred at SSAU was a disruption of the morphostatic synchrony between structure and culture brought about by new discourses and structures emanating from the broader international and national higher education context. In particular, it seems that attempts at reconciling the constraining contradictions between the discourses and structures related to quality assurance on the one hand and educational development on the other resulted in a conjunction between transformation at the levels of both the cultural system and social structure. This conjunction, along with the actions of key Institutional agents and the morphogenesis of the staff of the Educational Development Unit, created sufficiently enabling conditions in the Institution for the introduction of the PGDHE. The research adds to knowledge through insights into the contribution that the ideas, beliefs, values, ideologies and theories about higher education broadly and about educational development specifically make to enabling or constraining conditions for the professionalization of academic staff in higher education institutions. It uncovers how relevant structures at the international, national and institutional levels can shape the practice of educational development and specifically staff development. It has generated insights into how the relevant people and the positions they hold can impact on staff development practices. In summary, the research could contribute towards emancipatory knowledge which could be used by SSAU and educational development practitioners elsewhere to inform future planning and decision making in relation to educational development and more specifically staff development practices in their contexts.
Keywords: Teachers -- Training of -- South Africa; Education, Higher -- South Africa; Graduate students -- South Africa; Universities and colleges -- South Africa -- Graduate work